Revision of Tynacantha Dallas with description of two new species (Hemiptera: Heteroptera: Pentatomidae: Asopinae) - Brugnera, Ricardo; Campos, Luiz Alexandre; Grazia, Jocelia (Zootaxa, 2019)
Here, Tynacantha Dallas is revised and two new species are described from Brazil: T. cuprea Brugnera & Grazia sp. nov. and T. umeridenigrata Brugnera & Grazia sp. nov. The type material is analyzed, figures, illustrations, a distributional map and a key to the species are provided. The color variation found in T. marginata is also discussed.